The Role of Pegadaian Syariah in Increasing Community Financial Access : Case Studies in Communities in the District. Medan Area - Zamaluddin Sembiring; Mutawaqil Billah Tumanggor; Cynthia Syahni; Mhd Rasyid Siddiq; Muhammad Wahyu; Ramadhan Lugu; Tarmizi Tarmizi (Harmony Management: International Journal of Management Science and Business, 2025)
The purpose of this research is to analyze the opinions and perceptions of the community around the Medan Area District regarding the role of Pegadaian Syariah as a non-usury practice in increasing public financial access. This research is quantitative research. Data analysis was carried out by distributing questionnaires to the community around the Medan Area District both via E-Form and in person. This research was carried out at Sukaramai Market, Medan Area District. The data collection instrument consists of interview observation and documentation. Collecting data, researchers also used several measuring tools to determine the interests of Sukaramai market traders, Medan Area District, namely Knowledge, Information, Interest. To find out what the surrounding community thinks in this research, the researcher used interviews, namely by interviewing 3 people from the community around the Sukaramai market who are customers of the AR Hakim Branch Pegadaian Syariah.